2011
DOI: 10.1089/thy.2010.0337
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy Reference Intervals of Thyroid Hormone Concentrations in a Thyroid Antibody-Negative Pregnant Population

Abstract: These gestational age-specific reference intervals for thyroid hormones provide a framework for clinical decision making. Overweight and obesity are increasing problems among fertile women and they are associated with possibility of thyroid dysfunction during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
82
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 36 publications
13
82
2
6
Order By: Relevance
“…In that study, BMI averaged 2.9 kg/m 2 higher (17 lb) in association with FT4 concentrations below the 2.5th centile. Other recent studies have documented similar relationships (4)(5)(6)(7). Depending upon the nature of this relationship across the broader BMI or weight spectrum, a maternal weight effect might partially explain variations among individual FT4 ranges, thereby accounting for a portion of overall population variability.…”
Section: Introductionmentioning
confidence: 57%
“…In that study, BMI averaged 2.9 kg/m 2 higher (17 lb) in association with FT4 concentrations below the 2.5th centile. Other recent studies have documented similar relationships (4)(5)(6)(7). Depending upon the nature of this relationship across the broader BMI or weight spectrum, a maternal weight effect might partially explain variations among individual FT4 ranges, thereby accounting for a portion of overall population variability.…”
Section: Introductionmentioning
confidence: 57%
“…2 and Table 1), and both median TSH and upper and lower reference limits start decreasing (32,33,34,35,36). To emphasize that thyroid function test reference values are variable in pregnancy, but still keep evaluation somewhat simple, much focus has been Early pregnancy variation in test result in a woman who has no functional thyroid gland, but who was euthyroid on levothyroxine replacement therapy before becoming pregnant.…”
Section: Changes In Thyroid Function and Test Reference Limits In Prementioning
confidence: 99%
“…In the near future, tandem mass spectrometry, which has shown a very good correlation with equilibrium dialysis during gestation (76), may be the technique to be used for such purposes. Another factor to consider during pregnancy is the observed inverse relationship between FT 4 and weight (127,128). In this regard, the recent work of Medici et al (129) has shown a decrease in the weight of children born to mothers with FT 4 in the upper limit of normality.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%